Evaluasi Implementasi Tata Tertib Sekolah Dalam Meningkatkan Kedisiplinan Siswa Di SMP Negeri 23 Bengkulu Selatan - Herlena, Desi; Sumarsih (Manajer Pendididikan, 2024)
This study aims to evaluate disciplinary standards and obstacles experienced through the implementation of school rules in SMP Negeri 23 South Bengkulu. This study used a descriptive evaluation study approach. This research data was obtained through observation, interviews and documentation. The data analysis techniques used are reducing data, presenting data, and inferring data. The results showed that the evaluation of student discipline through the implementation of discipline is the habituation of school rules to students related to school entrance matters, student obligations, student prohibitions, clothing matters and sanctions, teachers become models so that students imitate what teachers do, and condition students to obey school rules and provide reprimands and sanctions for students who violate school rules. The obstacles encountered are teachers who cannot bear to give punishment to students, lack of awareness of students to obey the rules schooling, lack of parental attention and concern for children, and low family economy.